Limitations of enamel microabrasion technique applied in a pediatric patient: case report - Paschoal, Marco Aurélio Benini [UNESP]; Zuanon, Angela Cristina Cilense [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (My University, 2011)
Enamel microabrasion is a non-invasive method that removes intrinsic and superficial defects from teeth aimed to improve dental esthetic with minimal loss of dental tissue. This case presentation describes the attempt for teeth color correction utilizing that conservative technique in a young girl whose upper central incisor presented an opaque white stain. Scanning electron microscopy (SEM) was conducted in order to illustrate the glasslike luster and a smooth texture of microabraded enamel surface. The correct diagnosis of defect is a difficult task, when consider this conservative approach.

A microabrasão do esmalte é um método não-invasivo que remove defeitos intrínsecos e superficiais dos dentes objetivando melhorar a estética dentária com mínimo de perda estrutural. Este relato de caso descreve uma tentativa para a correção da cor dentária utilizando esta técnica conservativa numa paciente jovem cujo incisivo central superior apresentou uma mancha branco-opaca. Microscopia eletrônica de varredura (MEV) foi realizada de modo a ilustrar o aspecto de vidro lustrado e uma textura lisa da superfície do esmalte microabrasionado. O correto diagnóstico do defeito é uma tarefa difícil ao se considerar esta abordagem conservativa.
Limitações da técnica de microabrasão em esmalte aplicada em paciente pediátrico: relato de caso clínico
Keywords: Microabrasion; Dental enamel defects; Stains; Microabrasão; Defeitos do esmalte dentário; Manchas